Non-dimensional interaction curve for fire-exposed reinforced concrete section - Gaikwad, Mahesh; Gopalakrishnan, N.; Singh, Suvir; Bhargava, Pradeep (Journal of Structural Engineering, 2024)
Traditional fire-resistant design methods are primarily prescriptive in nature, which ensures that the overall dimensions of the Reinforced Concrete (RC) section and cover to the reinforcement. The design of RC sections subject to axial force and bending moment during a fire requires several tests involving lengthy calculations to achieve the desired fire resistance. The paper presents a sectional analysis method for heated RC sections that defines non-dimensional capacity parameters for interaction diagrams. The application of the interaction diagram is rendered more versatile by establishing non-dimensional parameters during the fire. The study includes a heat transfer analysis for determining the thermal profile and a sectional analysis to predict the interaction curve for different fire duration intervals. The RC section was exposed to a 2-hour ISO 834 fire and was modelled by making interaction diagram coordinates independent of cross-sectional dimensions and material properties. The study comprised three different percentages of steel. The findings of numerical studies are used to quantify the effects of reinforcement percentage on load capacity. The axial and flexural capacities for the given sectional dimensions and material properties could subsequently be modified in a redesign. The proposed approach enables the design and analysis of reinforced concrete structural elements to meet specified fire resistance requirements.